Comprehensive CFD simulation of the optimizations of geometric structures and operating parameters for industrial acetylene hydrogenation reactors. (23rd September 2016) - Tian, Liang; Hu, Guihua; Du, Wenli; Qian, Feng
Abstract: In this study, for the first time, comprehensive simulations of the industrial adiabatic and isothermal reactors utilized for the hydrogenation of acetylene were performed by computational fluid dynamics (CFD). The standard k–ϵ and Spalart‐Allmaras models were employed for describing the turbulence characteristics of the adiabatic and isothermal reactors, respectively. The porous medium model was applied to the flow of catalyst particles. The laminar finite‐rate model was employed for simulating the reaction in the reactor. The results obtained from simulations were in close agreement with those obtained from the industrial adiabatic reactor. Based on the validated CFD models, three operating conditions of the adiabatic reactor are simulated for comparing the selectivity of acetylene; as a result, H and T segmentation is utilized as an optimum process parameter. The different geometric structures of the adiabatic and isothermal reactors are simulated for obtaining the best diameter to length (D/L) ratio. The simulation results indicated an optimal D/L of 0.3852 for the adiabatic reactor, and the diameter‐to‐length ratio exerts a marginal effect on the reaction selectivity of isothermal reactors.